A method for optimizing tellurium alloy evaporation performance for rare earth doped CdTe solar panels

CN122959668APending Publication Date: 2026-10-23INNER MONGOLIA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611063368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有研究主要集中于稀土掺杂对CdTe薄膜光电性能的改善,关于稀土元素如何通过改变碲的晶体结构、表面结合能和缺陷密度来调控纯碲及碲合金的蒸发速率,其内在机制尚未被系统揭示

Benefits of technology

1.该发明通过特定原料体系的合金化设计,使制备得到的碲合金中In2Te5相与富Te相协同作用,In2Te5相热稳定性高,可有效抑制铟在高温下的蒸发行为,在350℃下无铟蒸发;富Te相的存在保障了碲的有效蒸发供给,从而实现碲蒸发量的精准调控,保障薄膜成分的稳定性和可控性,避免传统材料中因高温导致的成分偏移和产品污染问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959668A_ABST
    Figure CN122959668A_ABST
Patent Text Reader

Abstract

The application discloses a method for optimizing the evaporation performance of a tellurium alloy for a rare earth doped CdTe solar panel, which takes tellurium powder, indium powder and dysprosium powder as raw materials, and sequentially carries out raw material batching, vacuum tube sealing, programmed temperature rising smelting, balanced solidification cooling, alloy crushing, powder making and pressing forming treatment to obtain the tellurium alloy evaporation material; the obtained material at least contains In2Te5 phase and Te-rich phase; the application effectively reduces the saturated vapor pressure of tellurium through rare earth doping and alloying design; when the material is used for thermal evaporation, there is no indium element evaporation at 350 DEG C, the tellurium evaporation amount is less than 0.7wt%, and the tellurium vapor flux is large within the required time of the button shape, so that the tellurium volatilization loss in the high-temperature degassing stage can be significantly inhibited, the stable and controllable tellurium evaporation rate can be realized, the purity and uniformity of the evaporation film are improved, the method is suitable for the tellurium layer vacuum thermal evaporation process of the CdTe thin film solar cell, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of vacuum evaporation technology, specifically relating to a method for optimizing the evaporation performance of tellurium alloys for CdTe solar panels through rare earth doping. Background Technology

[0002] Tellurium (Te) is a key element in the preparation of compound semiconductor materials, possessing excellent optoelectronic properties, high carrier mobility, extremely low room-temperature lattice thermal conductivity, and good environmental stability. Tellurium's narrow band gap enables it to perform broad-spectrum detection, and its rich optoelectronic properties allow for diverse applications: cadmium telluride can be used to manufacture light-emitting diodes, radiation detectors, and solar cells; mercury-cadmium telluride alloys are core materials for infrared emitters and infrared detectors; and bismuth-selenium-antimony telluride alloys are important thermoelectric materials used for power generation and refrigeration, covering civilian products such as water dispensers, refrigerators, and air conditioners, as well as fields such as aerospace propulsion systems, aerospace, high-altitude weather recording instruments, military radar coolers, and submarine air conditioning systems.

[0003] The tellurium raw material used in the aforementioned high-end devices must have a purity of 4N or higher; otherwise, impurities will directly lead to a significant decrease in device performance. Therefore, the influence of impurities in the system is of particular concern in tellurium applications. Tellurium has a melting point of 450℃, enabling low-temperature growth. Common tellurium thin film preparation methods include thermal evaporation and magnetron sputtering. However, when using pure tellurium as an evaporation source and preparing tellurium layers at high temperatures, temperature control is extremely stringent. Pure tellurium is prone to uneven evaporation at high temperatures, which may be accompanied by co-evaporation of impurity elements, leading to unstable film composition and decreased performance. In addition, pure tellurium has a high saturated vapor pressure and begins to evaporate significantly at temperatures above 200℃, resulting in an excessively rapid evaporation rate at high temperatures, which seriously affects the reaction process or the quality of tellurium film formation. Furthermore, high-temperature degassing is often required before the high-temperature thermal evaporation reaction, which leads to a large amount of tellurium volatilization. This wastes raw materials, increases production costs, and also contaminates the chamber and affects film quality.

[0004] In specific applications of cadmium telluride (CdTe) thin-film solar cells, the aforementioned problems are particularly prominent. The mainstream process for preparing CdTe thin films—the near-space sublimation method—involves heating the CdTe or Te / Cd source material to its sublimation temperature, causing tellurium to evaporate and sublimate on a relatively cool substrate surface to form a CdTe thin film. However, pure tellurium exhibits significant evaporation flux even in the relatively low temperature range of 200°C to 300°C, a characteristic that predates the normal sublimation temperature window of CdTe. This results in the inability to achieve stable and controllable evaporation of the tellurium component during the heating and temperature control phases of the CSS process. The saturated vapor pressure of pure tellurium increases exponentially with increasing temperature; even small temperature fluctuations can cause significant drift in the evaporation flux, leading to uneven spatial distribution of film thickness and decreased batch-to-batch consistency. Furthermore, as the tellurium material in the evaporation source is gradually consumed, the surface state and composition distribution of the source material within the crucible continuously change. Even with constant temperature control parameters, the evaporation rate will still experience uncontrollable drift, directly limiting the precise control of film thickness and uniformity.

[0005] To address the issues of unstable pure tellurium evaporation rates and difficulty in controlling evaporation behavior, existing technologies attempt breakthroughs through process parameter optimization and equipment improvement, such as precisely controlling source and substrate temperatures, adjusting source-substrate distance, and optimizing deposition chamber pressure. However, existing tellurium alloy systems are complex and fail to effectively balance the contradiction between vapor pressure and tellurium evaporation suppression. Problems such as coarse grains or uneven phase distribution in the alloy can easily lead to compositional segregation during evaporation, reducing film uniformity; simultaneously, other elements in the alloy may evaporate simultaneously, introducing additional impurities and affecting product quality. Therefore, a novel alloy solution that starts from the material design stage and can precisely control tellurium evaporation behavior is urgently needed.

[0006] In recent years, the effects of rare earth doping on the properties of tellurium and telluride materials have gradually attracted attention. Studies have shown that rare earth elements, such as Nd and Dy, doping CdTe thin films can significantly affect the crystal structure, preferred orientation, grain size, and optical band gap of the films. Rare earth elements have a significant microstructure modification effect in tellurium alloys: they can act as nucleation sites to promote non-spontaneous nucleation, refining the alloy microstructure; they can cause lattice distortion, improving the microstructure morphology, increasing grain boundary density, thereby hindering dislocation movement and improving the thermal stability and mechanical properties of the alloy. However, existing research mainly focuses on the improvement of the photoelectric properties of CdTe thin films by rare earth doping. The underlying mechanism by which rare earth elements regulate the evaporation rate of pure tellurium and tellurium alloys by changing the crystal structure, surface binding energy, and defect density of tellurium has not yet been systematically revealed. If we can utilize rare earth doping to prepare novel tellurium alloys, optimize the evaporation characteristics of tellurium from the material source, and achieve stable and controllable evaporation rates over a wide temperature range, we can not only solve the serious volatilization problem of tellurium during the high-temperature degassing stage, but also provide a stable and uniform tellurium vapor flow during the deposition process, thereby significantly improving the thickness uniformity, process repeatability, and raw material utilization of cadmium telluride films.

[0007] In summary, it is necessary to provide a rare earth-doped modified tellurium alloy preparation method for use in the high-temperature thermal evaporation process of tellurium, so that it can be stably and for a long time to evaporate during the preparation of CdTe solar panels, effectively suppressing tellurium loss during high-temperature degassing, controlling the tellurium vapor flux per unit time, and avoiding the introduction of impurities due to the co-evaporation of alloy elements, thereby promoting the high-quality development of the cadmium telluride thin-film solar cell industry. Summary of the Invention

[0008] The purpose of this invention is to provide a method for optimizing the evaporation performance of tellurium alloys for CdTe solar panels by rare earth doping, so as to solve the problems mentioned in the background art.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels through rare earth doping, comprising the following steps: Step S1, Raw material preparation: Weigh tellurium powder, indium powder and dysprosium powder according to the mass ratio, and mix the three powders thoroughly to obtain a mixed powder. Step S2, Vacuum sealing: The mixed powder is loaded into a quartz glass tube, and the quartz glass tube is evacuated to the set vacuum level using a tube sealing machine and then vacuum sealed. Step S3, programmed heating and melting: Place the sealed quartz glass tube into a high-frequency melting furnace, raise the temperature to the target melting temperature using a segmented programmed heating method, hold the temperature for a set time, and obtain a completely molten alloy melt. Step S4, Equilibrium Solidification and Cooling: After melting, the alloy melt is subjected to equilibrium solidification and cooling at a constant rate to 400°C, and then naturally cooled to room temperature to obtain a solid alloy ingot. Step S5, Alloy Crushing and Powdering: Take out the solid alloy ingot, crush it, and sieve it to obtain alloy powder within the target particle size range; Step S6, Pressing and Molding Process: The alloy powder is placed into the mold of the tablet press and pressed into a button-shaped evaporation source blank, thus obtaining the rare earth-doped modified tellurium alloy evaporation material. The prepared tellurium alloy evaporation material includes at least the In2Te5 phase and the Te-rich phase.

[0010] In a preferred embodiment, the purity of the tellurium powder, indium powder, and dysprosium powder is 4N or higher.

[0011] In a preferred embodiment, the proportion of tellurium powder is 75% to 80%, the proportion of indium powder is 18% to 24.5%, and the proportion of dysprosium powder is 0.5% to 2% by mass fraction.

[0012] In a preferred embodiment, in step S2, the internal vacuum degree of the quartz glass tube before sealing is controlled within the range of 0.5 Pa to 100 Pa.

[0013] In a preferred embodiment, the specific process of segmented temperature increase in step S3 is as follows: the temperature is increased to 350°C at a rate of 10°C / min, then increased to 500°C at a rate of 5°C / min, and finally increased to 800°C at a rate of 1°C / min.

[0014] In a preferred embodiment, the target melting temperature is 800°C and the holding melting time is 90 minutes.

[0015] In a preferred embodiment, in step S4, the constant furnace cooling rate for equilibrium solidification is 0.4 K / s.

[0016] In a preferred embodiment, in step S5, the particle size range of the alloy powder after sieving is 100 mesh to 300 mesh.

[0017] As a preferred embodiment, when the prepared tellurium alloy evaporation material is used for hot evaporation, no indium evaporates at 350°C, the amount of tellurium evaporated is less than 0.7 wt%, and the amount of vapor required for the button-shaped material is large.

[0018] As a preferred embodiment, the prepared tellurium alloy evaporation material is applied to the tellurium layer vacuum thermal evaporation process for CdTe thin-film solar cells.

[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention, through the alloying design of a specific raw material system, enables the In2Te5 phase and the Te-rich phase in the prepared tellurium alloy to work synergistically. The In2Te5 phase has high thermal stability and can effectively suppress the evaporation behavior of indium at high temperatures, with no indium evaporation at 350°C. The presence of the Te-rich phase ensures an effective supply of tellurium for evaporation, thereby achieving precise control of the amount of tellurium evaporation, ensuring the stability and controllability of the film composition, and avoiding the composition shift and product contamination problems caused by high temperatures in traditional materials.

[0020] 2. This invention introduces dysprosium metal to form a stable alloy system with indium and tellurium, which effectively reduces the saturated vapor pressure of tellurium and ensures that no unnecessary element co-evaporation will occur under high temperature conditions, thus preventing the introduction of impurities. Combined with segmented programmed heating melting and balanced solidification processes, the alloy structure can be refined, component segregation and internal defects can be reduced, the material density and crystal uniformity can be improved, and the purity and uniformity of the vapor-deposited film can be guaranteed.

[0021] 3. This invention presses alloy powder into a button-shaped evaporation source, enabling the material to have a large tellurium vapor flux and stable output per unit time within the required temperature range of the process; the button-shaped dense molding structure has uniform thermal conductivity and high heating efficiency, which can effectively improve the efficiency and stability of thin film preparation, while improving the service life and long-term stability of the evaporation source.

[0022] 4. The tellurium alloy material prepared by this invention has extremely low tellurium evaporation during the high-temperature degassing stage in the early stage of hot evaporation, which can reduce raw material waste and chamber contamination; the material has excellent overall thermal stability and creep resistance, and the evaporation source can maintain stable performance after long-term thermal cycling. It can directly replace existing pure tellurium raw materials without additional process adjustments, and has significant industrial application value. Attached Figure Description

[0023] Figure 1 The XRD pattern of the composite material prepared in Example 1 of this invention; Figure 2 The SEM image of the composite material prepared in Example 1 of this invention; Figure 3 The TG spectrum of the composite material prepared in Example 1 of this invention; Figure 4 The XRD pattern of the composite material prepared in Example 2 of this invention; Figure 5 The SEM image of the composite material prepared in Example 2 of this invention; Figure 6 The TG spectrum of the composite material prepared in Example 2 of this invention; Figure 7 The XRD pattern of the composite material prepared in Example 3 of this invention; Figure 8The SEM image of the composite material prepared in Example 3 of this invention; Figure 9 The TG spectrum of the composite material prepared in Example 3 of this invention; Figure 10 The XRD pattern of the composite material prepared in Comparative Example 1 of this invention; Figure 11 The image shows the SEM image of the composite material prepared in Comparative Example 1 of this invention. Figure 12 The XRD pattern of the composite material prepared in Comparative Example 2 of this invention; Figure 13 The image shows the SEM image of the composite material prepared in Comparative Example 2 of this invention. Figure 14 The XRD pattern of the composite material prepared in Comparative Example 3 of this invention; Figure 15 This is the SEM image of the composite material prepared in Comparative Example 3 of the present invention. Detailed Implementation

[0024] The present invention will be further described below with reference to embodiments.

[0025] The following embodiments are used to illustrate the present invention, but should not be used to limit the scope of protection of the present invention. The conditions in the embodiments can be further adjusted according to specific conditions, and simple improvements to the method of the present invention under the premise of the concept of the present invention are all within the scope of protection claimed by the present invention.

[0026] Example 1 This embodiment provides a method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping. The raw material composition by mass fraction is: 75% tellurium powder (Te), 24.5% indium powder (In), and 0.5% dysprosium powder (Dy). The purity of the three powders is 4N.

[0027] The specific preparation steps are as follows: Step S1, Raw material preparation: Weigh 300g tellurium powder, 98g indium powder, and 2g dysprosium powder, and mix the three powders thoroughly to obtain a mixed powder. Step S2, Vacuum sealing: The mixed powder is loaded into a quartz glass tube, and a tube sealing machine is used to evacuate the tube to a vacuum level of 100 Pa, and then vacuum sealing is performed. Step S3, programmed temperature melting: Place the sealed quartz glass tube in a high-frequency furnace and heat it using a programmed temperature method: first, heat it to 350°C at a rate of 10°C / min, then to 500°C at a rate of 5°C / min, and finally to 800°C at a rate of 1°C / min. Then, heat it at 800°C for 90 minutes to obtain a completely molten alloy. Step S4, Equilibrium Solidification and Cooling: After melting, maintain a solidification rate of 0.4 K / s for equilibrium solidification, and cool to room temperature to obtain a solid alloy ingot. Step S5, Alloy Crushing and Powdering: Take out the alloy ingot, crush it, and sieve it to obtain 200-mesh alloy powder; Step S6, Pressing and Molding Process: The alloy powder is placed in a tablet press and pressed into a button-shaped evaporation source blank, thus obtaining the rare earth doped tellurium alloy evaporation material of this embodiment.

[0028] The composite material prepared in this embodiment was tested: the XRD pattern is shown below. Figure 1 As shown, the material consists of an In₂Te₅ phase and a trigonal Te phase. The diffraction peaks have very small full width at half maximum (FWHM), and no impurity peaks are observed, indicating good crystallinity. The SEM images are shown below. Figure 2 As shown, the composite material has a relatively uniform particle distribution and no voids on the surface. Thermogravimetric analysis indicates that, as Figure 3 As shown, the material exhibits no weight loss below 200℃, and at 350℃, the Te evaporation rate is approximately 0.5wt%, while In shows no weight loss. Using this material to prepare tellurium films, the composite material was added to a vapor deposition apparatus, sealed, and vented. The mixture was then heated to 300℃ for further degassing, followed by vapor deposition at 400℃ for a period of time. The resulting film was pure Te, with no detected In impurities. After prolonged high-temperature use, the surface particles of the material became loose, and occasional debris appeared.

[0029] Example 2 This embodiment provides a method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping. The raw material composition by mass fraction is: 80% tellurium powder (Te), 18% indium powder (In), and 2% dysprosium powder (Dy). The purity of the three powders is 4N.

[0030] The specific preparation steps are as follows: Step S1, Raw material preparation: Weigh 320g tellurium powder, 72g indium powder, and 8g dysprosium powder, and mix the three powders thoroughly to obtain a mixed powder. Step S2, Vacuum sealing: The mixed powder is loaded into a quartz glass tube, and a sealing machine is used to evacuate the tube to a vacuum level of 0.5 Pa, followed by vacuum sealing. Step S3, programmed temperature rise melting: Place the sealed quartz glass tube in a high-frequency furnace, maintain the vacuum degree in the furnace at 10 Pa, and heat it using a programmed temperature rise method: first, raise the temperature from room temperature to 350°C at a rate of 10°C / min, then raise it to 500°C at a rate of 5°C / min, and finally raise it to 800°C at a rate of 1°C / min, and hold it at 800°C for 90 min to obtain a completely molten alloy melt; Step S4, Equilibrium Solidification and Cooling: After melting, maintain a solidification rate of 0.4 K / s for equilibrium solidification, and cool to room temperature to obtain a solid alloy ingot. Step S5, Alloy Crushing and Powdering: Take out the alloy ingot, crush it, and sieve it to obtain 300-mesh alloy powder; Step S6, Pressing and Molding: Place the alloy powder in a tablet press and press it into a button-shaped evaporation source blank to obtain the rare earth doped tellurium alloy evaporation material of this embodiment.

[0031] The composite material prepared in this embodiment was tested: the XRD pattern is shown below. Figure 4 As shown, in addition to the In2Te5 phase and the trigonal Te phase, DyTe phase impurity peaks are present, with very small full width at half maximum (FWHM) peaks, indicating good material crystallinity; SEM measurements are as follows. Figure 5 As shown, the material distribution is uniform; thermogravimetric analysis is as follows. Figure 6 As shown, the material exhibits no weight loss below 200℃, with approximately 0.7wt% Te evaporation at 350℃ and no In weight loss. Thermal evaporation coatings using this material did not show any In elemental impurities in the film.

[0032] Example 3 This embodiment provides a method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping. The raw material composition by mass fraction is: 77% tellurium powder (Te), 22% indium powder (In), and 1% dysprosium powder (Dy). The purity of the three powders is 4N.

[0033] The specific preparation steps are as follows: Step S1, Raw material preparation: Weigh 308g tellurium powder, 88g indium powder, and 4g dysprosium powder, and mix the three powders thoroughly to obtain a mixed powder. Step S2, Vacuum sealing: The mixed powder is loaded into a quartz glass tube, and a tube sealing machine is used to evacuate the tube to a vacuum level of 100 Pa, and then vacuum sealing is performed. Step S3, programmed temperature melting: Place the sealed quartz glass tube in a high-frequency furnace and heat it using a programmed temperature method: first, raise the temperature from room temperature to 350°C at a rate of 10°C / min, then raise it to 500°C at a rate of 5°C / min, and finally raise it to 800°C at a rate of 1°C / min. Then, hold the temperature at 800°C for 90 minutes to obtain a completely molten alloy melt. Step S4, Equilibrium Solidification and Cooling: After melting, maintain a solidification rate of 0.4 K / s for equilibrium solidification, and cool to room temperature to obtain a solid alloy ingot. Step S5, Alloy Crushing and Powdering: Take out the alloy ingot, crush it, and sieve it to obtain 300-mesh alloy powder; Step S6, Pressing and Molding Process: The alloy powder is placed in a tablet press and pressed into a button-shaped evaporation source blank, thus obtaining the rare earth doped tellurium alloy evaporation material of this embodiment.

[0034] The composite material prepared in this embodiment was tested: the XRD pattern is shown below. Figure 7 As shown, the material corresponds to the In2Te5 phase and the trigonal Te phase, with DyTe phase impurity peaks present. The diffraction peaks have very small full width at half maximum (FWHM), and no impurity peaks are observed. SEM measurements are as follows: Figure 8 As shown, the material distribution is uniform; thermogravimetric analysis is as follows. Figure 9 As shown, the material exhibits no weight loss below 200℃, with approximately 0.6wt% Te evaporation at 350℃ and no In weight loss. Using this material to prepare tellurium films, the composite material was added to a vapor deposition apparatus, sealed and vented, then heated to 300℃ for further degassing, followed by vapor deposition at 400℃ for a period of time. The resulting film was pure Te phase, with no detected In impurities.

[0035] Comparative Example 1 The raw material composition of this comparative example is: 85% tellurium powder (Te), 14% indium powder (In), and 1% dysprosium powder (Dy). The purity of the three powders is 4N.

[0036] The preparation steps are as follows: Weigh 360g of tellurium powder, 56g of indium powder, and 4g of dysprosium powder and place them in a quartz glass tube. Vacuum the tube to 0.5Pa and then seal it. Place the quartz glass tube in a high-frequency furnace and use a programmed temperature rise: raise the temperature to 350℃ at a rate of 10℃ / min, then to 500℃ at a rate of 5℃ / min, and finally to 700℃ at a rate of 1℃ / min. Melt the tube at 700℃ for 90min. Allow the tube to cool naturally to room temperature under vacuum to obtain the alloy. Remove the alloy and crush it into 200-mesh powder, then press it into button shapes.

[0037] Tests on this comparative sample revealed the following: XRD patterns as follows Figure 10 As shown, in addition to the In2Te5 phase and the trigonal Te phase, there are also impurity peaks with slightly higher intensity, which, upon comparison, are Dy and DyTe related peaks; SEM measurements are as follows. Figure 11 As shown, the material distribution is uniform; thermogravimetric analysis shows that the Te evaporation rate at 350℃ is about 1.4wt%, and In has no weight loss; there is no In element in the vapor-deposited film layer, but the tellurium evaporation rate is too fast and difficult to control precisely.

[0038] Comparative Example 2 The raw material composition of this comparative example is: 75% tellurium powder (Te) and 25% indium powder (In). Both powders have a purity of 4N and no dysprosium powder is added.

[0039] The preparation steps are as follows: Weigh 300g of tellurium powder and 100g of indium powder, mix them and place them in a quartz glass tube, evacuate to 100Pa and seal it; place the quartz glass tube in a high-frequency furnace and use a programmed temperature rise: first raise the temperature from room temperature to 300℃ at a rate of 10℃ / min, then raise it to 450℃ at a rate of 5℃ / min, and finally raise it to 800℃ at a rate of 1℃ / min, and melt it at 800℃ for 90min; maintain a solidification rate of 0.4K / s to achieve equilibrium solidification and cool to room temperature to obtain the alloy; take out the alloy and crush it into 300-mesh powder, and press it into button shapes.

[0040] Tests on this comparative sample revealed the following: XRD patterns as follows Figure 12 As shown, no other impurity peaks were observed besides the In2Te5 phase and the trigonal Te phase; SEM measurements are as follows. Figure 13 As shown, the material distribution is uniform; thermogravimetric analysis shows that the Te evaporation rate at 350℃ is about 1.1wt%, and In has no weight loss; when using this material for thermal evaporation coating, there is no In in the film initially, but a small amount of In will appear in the film after a period of time, indicating insufficient stability in long-term use.

[0041] Comparative Example 3 The raw material composition of this comparative example is: 75% tellurium powder (Te), 24.5% indium powder (In), and 0.5% dysprosium powder (Dy). The purity of the three powders is 4N.

[0042] The preparation steps are as follows: Weigh 300g of tellurium powder, 98g of indium powder, and 2g of dysprosium powder and place them in a quartz glass tube. Vacuum the tube to 100Pa and then seal it. Place the quartz glass tube in a high-frequency furnace and use a programmed temperature rise: raise the temperature to 350℃ at a rate of 10℃ / min, then to 500℃ at a rate of 5℃ / min, and finally to 800℃ at a rate of 1℃ / min. Melt the tube at 800℃ for 90min. Allow the tube to cool naturally to room temperature under vacuum to obtain the alloy. Remove the alloy and crush it into 200-mesh powder.

[0043] Tests on this comparative sample revealed the following: XRD patterns as follows Figure 14 As shown, no impurity peaks were observed except for the In2Te5 phase and the trigonal Te phase; SEM measurements are as follows. Figure 15 As shown, the material distribution is uniform; thermogravimetric analysis shows that the Te evaporation amount at 350℃ is about 0.4wt%, and there is no In weight loss; there is no In element in the vapor-deposited film layer.

[0044] Comparative Example 4 This comparative example uses commercially available pure tellurium material with a purity of 99.99% as the evaporation source and uses it for thermal evaporation deposition to prepare tellurium film. Thermal evaporation deposition test found that when the deposition temperature is raised to 150℃ and above, the film surface becomes less dense, the saturated vapor pressure of pure tellurium material is too high, the evaporation rate is difficult to control, and the tellurium volatilization loss is serious during the high-temperature degassing stage.

[0045] As can be seen from the test results of the above embodiments and comparative examples, the tellurium alloy material prepared by the technical solution of the present invention can effectively optimize the evaporation performance of tellurium. The button-shaped material has a large tellurium vapor flux at the required temperature and per unit time. There is basically no tellurium evaporation loss during the high-temperature degassing stage. The prepared tellurium film is pure phase Te with good crystallization and no impurities such as indium.

[0046] The above experimental results show that introducing a certain amount of dysprosium can form a stable intermetallic compound with indium and tellurium, reducing the activity of Te / In; pressing it into a button shape can increase the evaporation area and improve the tellurium vapor flux per unit time; the staged melting and balanced solidification process in the preparation method can effectively adjust the crystallization characteristics and reduce defects; the tellurium alloy composite material prepared by this invention can meet the industrial demand for thermally vaporized tellurium film, can directly replace the current pure tellurium raw materials without additional processing, and has significant industrial application value.

[0047] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for optimizing the evaporation performance of tellurium alloys for CdTe solar panels through rare earth doping, characterized in that, Includes the following steps: Step S1, Raw material preparation: Weigh tellurium powder, indium powder and dysprosium powder according to the mass ratio, and mix the three powders thoroughly to obtain a mixed powder. Step S2, Vacuum sealing: The mixed powder is loaded into a quartz glass tube, and the quartz glass tube is evacuated to the set vacuum level using a tube sealing machine and then vacuum sealed. Step S3, programmed heating and melting: Place the sealed quartz glass tube into a high-frequency melting furnace, raise the temperature to the target melting temperature using a segmented programmed heating method, hold the temperature for a set time, and obtain a completely molten alloy melt. Step S4, Equilibrium Solidification and Cooling: After melting, the alloy melt is subjected to equilibrium solidification and cooling at a constant rate to 400°C, and then naturally cooled to room temperature to obtain a solid alloy ingot. Step S5, Alloy Crushing and Powdering: Take out the solid alloy ingot, crush it, and sieve it to obtain alloy powder within the target particle size range; Step S6, Pressing and Molding Process: The alloy powder is placed into the mold of the tablet press and pressed into a button-shaped evaporation source blank, thus obtaining the rare earth-doped modified tellurium alloy evaporation material. The prepared tellurium alloy evaporation material includes at least the In2Te5 phase and the Te-rich phase.

2. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, The purity of the tellurium powder, indium powder, and dysprosium powder is 4N or higher.

3. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, By mass fraction, the tellurium powder accounts for 75% to 80%, the indium powder accounts for 18% to 24.5%, and the dysprosium powder accounts for 0.5% to 2%.

4. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, In step S2, the internal vacuum degree of the quartz glass tube before sealing is controlled within the range of 0.5 Pa to 100 Pa.

5. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, In step S3, the specific process of segmented temperature increase is as follows: increase to 350°C at a rate of 10°C / min, then increase to 500°C at a rate of 5°C / min, and finally increase to 800°C at a rate of 1°C / min.

6. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 5, characterized in that, The target melting temperature is 800℃, and the holding melting time is 90min.

7. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, In step S4, the constant furnace cooling rate for equilibrium solidification is 0.4 K / s.

8. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, In step S5, the particle size range of the alloy powder after sieving is 100 mesh to 300 mesh.

9. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, When the prepared tellurium alloy evaporation material is used for hot evaporation, no indium evaporates at 350℃, the evaporation amount of tellurium is less than 0.7wt%, and the tellurium vapor flux is large within the time required for button-shaped evaporation.

10. The method for optimizing the evaporation performance of tellurium alloy for CdTe solar panels by rare earth doping according to claim 1, characterized in that, The prepared tellurium alloy evaporation material was applied to the vacuum thermal evaporation process of tellurium layer preparation for CdTe thin-film solar cells.